Care and pedagogical production: integration of Public Health System scenarios - Túlio Batista Franco; Elaine Barros Moreira (Faculdade de Medicina de Botucatu (Unesp), 2007)
Throughout Brazilian Public Health System's (Centralized Health System - SUS) construction history there has been a reasonable investment in the education for the sector. However, it has been frequently noticed by health professionals and managers the fact that this investment in educational programs has not converted into change of healthcare practices. Assuming that education can be used as a tool for changes in health, the text suggests that the pedagogical practices should be directed towards the production of individuals implied with the care production. Hence it proposes to work on a field of subjectivity in addition to cognition. This work reveals the management of the Brazilian public health system and its flows of permanent education, focusing "micromanagement" to think about the context on which they structuralize the diverse scenarios of care production, treating them as Pedagogical Production Units where it would be possible to develop entailed educational methodologies to a general idea of permanent education in health.